Fate of Forgotten DJ Stent - Thapa, Bikash Bikram; Thapa, Naryan; Bhandari, Bharat Bahadur (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: Double J stent is one common armamentarium used in urological procedure. It can serve both therapeutic and prophylactic function. However the use of double J stent is invariably associated with minor to some of major complications. Forgotten DJ stent is one untoward issue of stenting patient that is largely preventable and entails complex urological procedure to remove it. Methods: We performed descriptive study where data were collected prospectively from patients who have double J ureteral stent in situ after urological procedure. Stent left more than three months was defined as forgotten DJ stent. Demographic characteristics, clinic-radiological data and details of management were noted to evaluate the mode of presentation, associated complications and mode of treatment. The reason behind forgetting those stent was asked with study population and presented. Results: The total of 27 cases of forgotten DJ stent cases were recorded during period of December 2013 to January 2018. Mean age of patient was 46.6 ± 12.25 years. The longest indwelling time was 10 years. Stent syndrome was common mode of presentation followed by encrustation. Majority (92.5%) of the patients were managed with endourological approach and 26% (7) of cases required more than one modalities of treatment. Conclusions: The forgotten stent is an avoidable condition through proper patient counselling. When required the management necessitates simple cystoscopic to complex endourolgical intervention.